USING REMOTE SENSING AND GIS-TECHNIQUES IN SOUTH EAST CASPIAN COASTAL CHANGES DETECTION - S. R. Mousavi; K. Solaimani (Юг России: экология, развитие, 2015)
Remote sensing and GIS techniques have been used to detect the shoreline changes along Miankaleh peninsula promontory of the Gorgan Bay entrance over the last three decades (1975-2002). For this purpose satellite data including LANDSAT ETM+, TM, SPOT, ASTER L1A and RADARSAT have been analyzed. SPOT-Pan data were georeferenced with respect to 1 : 50 000 topographic maps using a Universal Transverse Mercator (UTM) projection, then all the needed data sets were registered to the SPOT-Pan image. The hydrological data showed a rapid rise of the Caspian Sea level by 2.6 m between “1975-1996”.